2005
DOI: 10.1177/0272989x05280558
|View full text |Cite
|
Sign up to set email alerts
|

Preference-Based Antithrombotic Therapy in Atrial Fibrillation: Implications for Clinical Decision Making

Abstract: For patients with atrial fibrillation, treatment recommendations from clinical practice guidelines often differ from patient preferences, with substantial heterogeneity in their individual preferences. Since patient preferences can have a substantial impact on the clinical decision-making process, acknowledgment of their importance should be incorporated into clinical practice guidelines. Practicing physicians need to balance the patient preferences with the treatment recommendations from clinical practice gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 59 publications
2
42
0
Order By: Relevance
“…49,51 More recent SDM studies in AF have reported decreased decisional conflict (the state of uncertainty surrounding a decision, a more accurate measure of the quality of the decision-making process because regret is strongly affected by the outcome the patient experiences, not the communication of the visit), increased patient satisfaction, and a trend toward increased knowledge compared with "traditional counseling" or guideline-based therapies groups, yet the findings have not been consistent. [52][53][54][55][56] Table 3 summarizes the evidence from these studies. 49,[52][53][54][55][56] However, it is critical to note that with the advent of the novel anticoagulants mentioned above since these studies, the number of options for stroke prevention has more than doubled, making this a far more complex decision.…”
Section: Sdm In Thromboembolism Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…49,51 More recent SDM studies in AF have reported decreased decisional conflict (the state of uncertainty surrounding a decision, a more accurate measure of the quality of the decision-making process because regret is strongly affected by the outcome the patient experiences, not the communication of the visit), increased patient satisfaction, and a trend toward increased knowledge compared with "traditional counseling" or guideline-based therapies groups, yet the findings have not been consistent. [52][53][54][55][56] Table 3 summarizes the evidence from these studies. 49,[52][53][54][55][56] However, it is critical to note that with the advent of the novel anticoagulants mentioned above since these studies, the number of options for stroke prevention has more than doubled, making this a far more complex decision.…”
Section: Sdm In Thromboembolism Preventionmentioning
confidence: 99%
“…[52][53][54][55][56] Table 3 summarizes the evidence from these studies. 49,[52][53][54][55][56] However, it is critical to note that with the advent of the novel anticoagulants mentioned above since these studies, the number of options for stroke prevention has more than doubled, making this a far more complex decision.…”
Section: Sdm In Thromboembolism Preventionmentioning
confidence: 99%
“…We do not address the threshold of absolute stroke risk for which anticoagulation is warranted, because this depends on additional considerations, including estimated bleeding risk during anticoagulation, 41 access to quality anticoagulation monitoring, and patient preferences and values. 42 Several million people with atrial fibrillation now receive chronic anticoagulation to prevent stroke. Additional research to identify more discriminating and accurate risk models around which standard recommendations could be developed would encourage more uniform use of antithrombotic agents and would likely lead to better patient outcomes.…”
Section: Stroke Risk In Atrial Fibrillation Working Group Stroke Riskmentioning
confidence: 99%
“…45 Warfarin needs to be dose adjusted with regular monitoring to ensure that the patient stays within the recommended therapeutic international normalised ratio (INR) range, making warfarin unacceptable to some patients. 46,47 Warfarin also has interactions with other medications including over-the-counter preparations, foods high in vitamin K and alcohol, which can impact on quality of life, meaning that some patients are reluctant to take warfarin. Recent NICE guidance DG14 48 has recommended coagulometers, devices that allow patients to self-monitor the INR, which is an alternative to regular INR monitoring, although some patients have experienced difficulties gaining access and support for these devices [Diane Eaton, AntiCoagulation Europe (ACE), 2016, personal communication].…”
mentioning
confidence: 99%